Research of compressed sensing for predistortion with relatively low sampling frequency - Xin HU; Jian-kang WANG; Fei LIU; Lian-jun OU; Jun LIANG; Gang WANG; Ji-run LUO (Tongxin xuebao)
In order to improve the TWTA digital predistortion linearizer with relatively low sampling frequency, the LUT and indirect learning architecture were used, which was cumbersome. A digital predistortion linearizer with compressed sensing technology was presented, which can provide good linearity improvement with simple and stable way.